2001
DOI: 10.1063/1.1391443
|View full text |Cite
|
Sign up to set email alerts
|

Guanine tautomerism revealed by UV–UV and IR–UV hole burning spectroscopy

Abstract: The vibronic spectrum of laser desorbed and jet cooled guanine consists of bands from three different tautomers of guanine as revealed by UV-UV and IR-UV double resonance spectroscopy. 1-methylguanine, in which the Keto-Enol tautomerism is blocked, shows hole burning spectra from the 9H-and 7H-Keto form. A comparison of the vibronic pattern of the different tautomers demonstrates that the vibronic spectrum built on the redmost guanine band at 32 870 cm Ϫ1 ͑electronic origin 0͒ can be traced back to the 9H-Enol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
243
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(278 citation statements)
references
References 25 publications
34
243
1
Order By: Relevance
“…Numbers are relative energies in cm -1 . Panels (e), (g) and (h) show experimental IR-UV double resonance spectra from Nir et al (31). The labels A-D refer to the four tautomers observed in REMPI spectroscopy.…”
Section: Monomers and Tautomeric Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numbers are relative energies in cm -1 . Panels (e), (g) and (h) show experimental IR-UV double resonance spectra from Nir et al (31). The labels A-D refer to the four tautomers observed in REMPI spectroscopy.…”
Section: Monomers and Tautomeric Formsmentioning
confidence: 99%
“…Nir et al obtained IR-UV DRS spectra of a series of guanosines, some of which appear in Figure 2 (31). Trace (a) shows 9H enol guanine (trace (c) in Figure 2) for comparison.…”
Section: Purinesmentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2012 stable conformers in the gas phase, [52][53][54] 62 although an earlier simulation suggested that the C 6 pucker CI may also be involved. 65 In the solution phase, Gua itself is rarely studied as it has poor solubility, although dGMP -has been studied in a number of experiments with transient absorption 1,16,66 and fluorescence upconversion.…”
Section: Dgmp -mentioning
confidence: 99%
“…Traditionally, resonant two-photon ionization (R2PI) and optical double resonance spectroscopies [5][6][7][8][9] have been used to study the guanine tautomers produced via laser desorption. However, Choi and Miller 10 showed that the tautomer distribution observed by IR spectroscopy of guanine formed by thermal vaporization with subsequent entrainment in ultracold helium droplets differs from that observed in laser desorption probed by R2PI.…”
mentioning
confidence: 99%